2019
DOI: 10.3390/ijms20225763
|View full text |Cite
|
Sign up to set email alerts
|

Y-chromosome and Surname Analyses for Reconstructing Past Population Structures: The Sardinian Population as a Test Case

Abstract: Many anthropological, linguistic, genetic and genomic analyses have been carried out to evaluate the potential impact that evolutionary forces had in shaping the present-day Sardinian gene pool, the main outlier in the genetic landscape of Europe. However, due to the homogenizing effect of internal movements, which have intensified over the past fifty years, only partial information has been obtained about the main demographic events. To overcome this limitation, we analyzed the male-specific region of the Y c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…In Hungary, 16.74% of men carry this haplotype [21]. I2a-P37 and subgroups occur at high frequencies in Sardinia (38.9% [63]) and are also present at high frequency among Balkan populations [64]. The proportion of the I2a1a Y type in the Romanian population is 17.7% [64].…”
Section: Haplogroup-based Analysesmentioning
confidence: 98%
“…In Hungary, 16.74% of men carry this haplotype [21]. I2a-P37 and subgroups occur at high frequencies in Sardinia (38.9% [63]) and are also present at high frequency among Balkan populations [64]. The proportion of the I2a1a Y type in the Romanian population is 17.7% [64].…”
Section: Haplogroup-based Analysesmentioning
confidence: 98%
“…15 Detailed studies of Y chromosome haplotypes have revealed male migration patterns throughout history and led to an understanding of the origins of current human populations. 16,17,18,19,20 These studies contributed to the development of a standardized Y-DNA phylogenetic tree maintained by the International Society of Genetic Genealogy (ISOGG). 21 European Y chromosomes are primarily comprised of the haplogroups E, G, I, J, N and R, with the R haplogroup comprising the majority of the Y chromosomes.…”
Section: Introductionmentioning
confidence: 99%
“…In Hungary, 16.74% of men carry this haplotype [14]. I2a-P37 and subgroups occur at high frequencies in Sardinia (38.9% [57]), and are also present at high frequency among Balkan populations [58]. The proportion of the I2a1a Y type in the Romanian population is 17.7%.…”
Section: Resultsmentioning
confidence: 99%